The Tudors - Morris, Christopher (Glasgow : Fontana/Collins, 1981)
Cultuur, politiek en de Tudors, de erfenis van de Tudors, Henri VII (1485-1509), Henri VIII (1509-1547), Edward VI (1547-1553), Mary Tudor (1553-1558), Elisabeth I (1558-1603)